EPAS1 and EGLN1 associations with high altitude sickness in Han and Tibetan Chinese at the Qinghai–Tibetan Plateau - Buroker, Norman E.; Ning, Xue-Han; Zhou, Zhao-Nian; Li, Kui; Cen, Wei-Jun; Wu, Xiu-Feng; Zhu, Wei-Zhong; Scott, C. Ronald; Chen, Shi-Han (Blood cells, molecules, & diseases, 2012)
High altitude sickness (HAS) occurs among humans visiting or inhabiting high altitude environments. Genetic differences in the EPAS1 and EGLN1 genes have been found between lowland (Han) and highland (Tibetan) Chinese. Three SNPs within EPAS1 and EGLN1 were evaluated in Han and Tibetan patients with acute mountain sickness (AMS) and chronic mountain sickness (CMS). We compared 85 patients with AMS to 79 Han unaffected with mountain sickness (MS) as well as 45 CMS patients to 34 unaffected Tibetan subjects. The three SNPs studied were EPAS1 [ch2: 46441523 (hg18], EGLN1 (rs480902) and (rs516651). Direct sequencing was used to identify individual genotypes for the three SNPs. Age was found to be significantly associated with the EPAS1 SNP in the CMS patients while heart rate (HR) and oxygen saturation level of hemoglobin (SaO2) were found to be significantly associated with the EGLN1 (rs480902) SNP in the Han patients with AMS. The individuals with CMS were found to diverge significantly for the EPAS1 SNP compared to their Tibetan control group as measured by genetic distance (0.123) indicating positive selection of the EPAS-G allele with age and illness. The EGLN1 (rs480902) SNP had a significant correlation with hematocrit (HCT), HR and SaO2 in AMS patients. AMS and CMS were found to be significantly associated with the EPAS1 and EGLN1 SNPs compared to their Han and Tibetan control groups, respectively, indicating these nucleotide alterations have a physiological effect for the development of high altitude sickness.